Development of Interactive Learning Media Assisted by Lectora Inspire Application in Science Subjects Class IV SDN Baru 03 Pagi - Siti Madiyah, Khoidah; Mulyawati, Ima (Paedagogia: Jurnal Pendidikan, 2023)
Researchers and developers are hard at work on new learning media, one of which is the Lectora Inspire application media, to counteract student indifference in homework and a rising lack of incentive to learn. The study technique is based on the 4D development paradigm (Define, Design, Develop, and Disseminate). The study's goal is to determine whether the media developed can be used and to collect data on how students react to the media. The goal of this study was to assess the performance of lecturers and professors serving as media and material validators, as well as students serving as respondents. Material experts validate 92.78% of the time, while media experts validate 91.78% of the time; expert teachers on average 85.00%; and students with an average of 89.52%. With the help of the Lectora Inspire software, it is clear that the potential for interactive learning media is enormous as a teaching tool.